2-Hydroxy-N′-(4-isopropylcyclohexylcarbonyl)-3-methylbenzohydrazide - Shu, Tian-Pin (International Union of Crystallography, 2009)
The crystal structure of the title compound, C(18)H(26)N(2)O(3), is stabilized by intermolecular N—H⋯O and O—H⋯O hydrogen bonds. One of the methyl groups is disordered with occupancies of 0.51 (3):0.49 (3).